Taxonomic notes on subgenus Steneotarsonemoides (Acari: Tarsonemidae) with description of a new species of Steneotarsonemus from Tiger grass in the northern hill zone of West Bengal, India - Ganguly, Moumi; Mondal, Priyankar; Karmakar, Krishna (Zootaxa, 2021)
A new species of tarsonemid mite, Steneotarsonemus amlisoae sp. nov. collected from tiger grass Thysanolaena latifolia (Poaceae) is described with illustrations of adult female, male and larva. The new species is the fourth species of Steneotarsonemus described from India. The species shares a lot of similarities with S. konoi but differ by apodeme architecture, cheliceral structure, setal length and positions. A taxonomic note on subgenus Steneotarsonemoides is provided.